Sorting the red tilapia - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Sorting of the tilapia fish at Orange Grove, Tacarigua
Cataloger's title
Keywords: Fishing -- Catch effort -- Trinidad and Tobago; Tilapia -- Trinidad and Tobago; Caroni (1975) Limited